Development of a protective inactivated vaccine against Crimean-Congo hemorrhagic fever infection - Berber, Engin; Canakoglu, Nurettin; Tonbak, Sukru; Ozdarendeli, Aykut (Cell Press, 2022)
Crimean-Congo hemorrhagic fever (CCHF) is an emerging zoonotic infectious disease caused by Crimean-Congo hemorrhagic fever virus (CCHFV). The first clinical CCHF infection was described in 1944 in the Crimean Peninsula, exclusively in humans, with case-fatality rates exceeding 30%. The increasing number of cases, high mortality rate, and lack of effective therapy make CCHF a serious threat to public health and a potential bioterrorism agent. The present study evaluated the development, immunogenicity, and immune response durations for cell-culture-derived inactivated vaccine (CCVax) formulations in comparison with those of mouse-brainderived vaccine (MBVax) formulations. In this study, the Kelkit06 CCHF virus strain was propagated in both suckling mice and Vero E6 cells, and purified with a sucrose gradient. Formalin-inactivated vaccine candidates were formulated at various doses [low dose (LD), 5 mu g; medium dose (MD), 10 mu g; high dose (HD), 20 mu g)] and mixed with an alum adjuvant. BALB/c mice received the same doses of the vaccine formulations three times at 3week intervals. The humoral endpoint IgG responses were evaluated and compared for the MBVax and CCVax treatments. The duration of the presence of IgG and neutralizing antibody (Ab) titers was evaluated and compared until up to 1 year after immunization. The humoral IgG responses indicated that the CCVax and MBVax candidates enhanced the IgG endpoint titers in a dose-dependent manner, which were induced more strongly in all the CCVax groups than in the MBVax mice. The fold changes in neutralizing Ab levels were also found to be higher in the CCVax groups: between 2- and 7.6-fold after the second week of the last immunization. The neutralization titers peaked 4 months after immunization in all the vaccine-receiving groups, but these were still comparable at the end of the first year. The CCVax formulations induced higher IgG and neutralizing Ab titers at all the measured time points. In this study, we showed that cell-culture-purified and formalin-inactivated vaccine candidates induced strong and robust immunity in vaccinated mice dose-dependently, more so than mouse-brain-derived vaccines.
Keywords: Crimean-Congo hemorrhagic fever virus; Bunyavirus; Hemorrhagic fever; Inactivated vaccine; Protective response; Long-term immunity; Humoral immune response